PERTUMBUHAN BAKTERI STAPHYLOCOCCUS AUREUS PADA MEDIA YANG DIEKSPOS DENGAN INFUS DAUN SAMBILOTO (ANDROGRAPHIS PANICULATA) - Retnowati, Yuliana; Bialangi, Nurhayati; Posangi, Nona Wingti (Sainstek, 2011)
The aim of study was to determine the growth of Staphylococcus aureus on The Medium that Exposed with sambiloto leaf infusion. The study was done at microbiology laboratory, Biology Department, Gorontalo State University. The descriptive method was used, that describes of the effect of sambiloto leaf infusion to S. aureus growth, which refers to the specific growth rate and generation time in bitter leaf infusion concentration variation during the incubation period 72 hours. The results showed that the sambiloto leaf infusion have bacteriostatic effect on S. aureus growth with specific growth rates at concentrations (v/v) of 0%, 25%, 50% and 75% were 0.362, 0.260, 0.169 and 0.974 / h and each of generation time were 1.92, 2.66, 4.09 and 9.29 hours. Keywords: Growth, S. aureus, infusion sambiloto leaf, bacteriostatic effect.